The impact of ILRI research on gender - Hill, Catherine; Haan, Nicoline C. de; Galiè, Alessandra; Njiru, Nelly (CAB International, 2020)
This chapter discusses the evolution of gender research at the International Livestock Research Institute (ILRI) and its predecessors, and in the context of CGIAR. It then reviews the impact of ILRI's gender research in a number of areas including development, science, capacity and policy.